Peculiarities of lytic action of melittin and its analog [Ala-14] melittin - Rudenko, S. V.; Madanat, Wajdi Khalaf Jamil (Biophysical Bulletin, 2005)
It is shown that lytic peptides melittin (M), melittin analog [Ala-14]melittin (P14A), and whole bee venom act in a different manner relative to human red blood cells (RBC). The normalized rate of hemolysis depended linearly on the relative amount of P14A in the mixture with both melittin and bee venom. The dose-response curve for P14A showed saturation only when the lytic effect of membrane-bound melittin was inhibited by chlorpromazine. This indicates that melittin and P14A produce hemolysis acting independently on each other. In contrast to melittin, but similar to bee venom, P14A also reduced the volume of lysed cells. Non-linear effects of cells shrinkage induced by mixtures of P14A with melittin and bee venom suggest that synergistic action of peptide analogs underlies the mechanism of this phenomenon. In addition, data suggest that melittin and P14A produce lytic effects through binding to different classes of sites on the RBC membrane. We conclude that the structure of lytic peptide is a predominant factor which in concert with the mode of peptide-membrane interactions modulates its lytic power.